1992
DOI: 10.1084/jem.175.6.1547
|View full text |Cite
|
Sign up to set email alerts
|

Membrane cofactor protein (CD46) protects cells from complement-mediated attack by an intrinsic mechanism.

Abstract: SummaryThe cleavage of C3 is a critical step for complement (C) activation in the classical and alternative pathways. This reaction is controUed by the regulators of C activation protein family. Membrane cofactor protein (MCP) is a cofactor for the factor I-mediated inactivation of C3b and C4b. As a widely distributed membrane protein, MCP may protect host cells from inadvertent C activation. Human MCP has recently been shown to protect transfected rodent cells from human C-mediated lysis. In this report the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(89 citation statements)
references
References 23 publications
2
85
2
Order By: Relevance
“…But MCP lacks receptor function. It inefficiently binds C3b-or C4b-bearing fluid-phase or cell-bound immune complexes (1,45). Thus, MCP's role is to transiently interact with either of these ligands bound to its "home" cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But MCP lacks receptor function. It inefficiently binds C3b-or C4b-bearing fluid-phase or cell-bound immune complexes (1,45). Thus, MCP's role is to transiently interact with either of these ligands bound to its "home" cell.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3, and 7). MCP binds these two ligands efficiently if they are attached to the same cell on which MCP itself is expressed (45). But MCP lacks receptor function.…”
Section: Discussionmentioning
confidence: 99%
“…One group of proteins, including CD55/ decay accelerating factor (DAF) and CD46/membrane cofactor protein (MCP), inhibits the classical and alternative pathway C3/C5 convertase enzymes. 24,25 Another set of proteins including CD59 regulates MAC assembly. 26 CRPs have been used to prevent rejection of xenotransplanted tissues and have also been shown to protect viruses and viral vectors from complement inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of cell-associated MCP function have relied principally on cytotoxicity assays of transfectants in whole serum (2,19,20). As an initial approach for directly assaying MCP's function on the cell surface, biotinylated C3b was deposited during the last amplification step (see Materials and Methods) on E rab C3b (18) showed that 2.1 Ϯ 0.2% of the added protein uniformly incorporated, and preliminary control experiments showed that the proteins incorporated with equal efficiencies (DAF, 2.1 Ϯ 0.3%; MCP, 1.9 Ϯ 0.2%).…”
Section: Daf Is Required For Mcp's Function In the Presence Of Excessmentioning
confidence: 99%